Interrogation of the Pathogen Box reveals small molecule ligands against the mycobacterial trehalose transporter LpqY-SugABC. Issue 10 (16th August 2022) - Radhakrishnan, Anjana; Brown, Chelsea M.; Guy, Collette S.; Cooper, Charlotte; Pacheco-Gomez, Raul; Stansfeld, Phillip J.; Fullam, Elizabeth
Abstract : Interrogation of the Pathogen Box identified diverse chemical scaffolds against the mycobacterial trehalose transporter. Abstract : Tuberculosis, caused by Mycobacterium tuberculosis, claims ∼1.5 million lives annually. Effective chemotherapy is essential to control TB, however the emergence of drug-resistant strains of TB have seriously threatened global attempts to control and eradicate this deadly pathogen. Trehalose recycling via the LpqY-SugABC importer is essential for the virulence and survival of Mtb and inhibiting or hijacking this transport system is an attractive approach for the development of novel anti-tubercular and diagnostic agents. Therefore, we interrogated the drug-like compounds in the open-source Medicines for Malaria Pathogen Box and successfully identified seven compounds from the TB, kinetoplastids and reference compound disease sets that recognise LpqY. The molecules have diverse chemical scaffolds, are not specific trehalose analogues, and may be used as novel templates to facilitate the development of therapeutics that kill Mtb with a novel mechanism of action via the mycobacterial trehalose LpqY-SugABC transport system.